Un tast dels vocabularis bilingües valencians actuals - Colomina i Castanyer, Jordi (Caplletra. Revista Internacional de Filologia, 2015)
By means of a choice of seventy words, this work shows the lexical richness and the degree of acceptance of the guidelines –defined in the Diccionari General de Llengua Catalana by Pompeu Fabra– regulating nine bilingual Valencian/Castilian and Castilian/Valencian vocabularies published between 1972 and 1993.